The improvement of learners linguocultural proficiency in English language instruction - Rakhimov, Mansur (The Lingua Spectrum, 2025)
This article delves into the critical concept of “linguocultural competence” within English language instruction, moving beyond traditional understandings of linguistic proficiency. This multi-faceted capability recognizes that true command of English necessitates more than grammatical accuracy and an extensive lexicon; it demands a deep comprehension of the cultural frameworks, historical contexts, and societal norms inherently embedded within the language itself. Indeed, the contemporary landscape of English Language Teaching (ELT) methodologies increasingly acknowledges the inextricable link between language, history, and culture. This paradigm shift reflects a growing consensus that language is not merely a neutral tool for communication but a dynamic repository of collective memory, values, and worldviews, shaping and being shaped by the communities that use it. Crucially, the recognition of this profound cultural component is intimately intertwined with the application of a cognitive approach in language research. This perspective argues that effective language acquisition and use are not just about memorizing rules or vocabulary, but about developing the cognitive schemas and processing abilities required to interpret, understand, and produce language in culturally appropriate and meaningful ways, thereby allowing learners to navigate the complex social and cultural dimensions of English communication with authenticity and competence.